AlCl3-mediated heteroarylation-cyclization strategy: one-pot synthesis of fused quinoxalines containing the central core of Lamellarin D. Issue 54 (16th May 2016) - Kumar, K. Shiva; Meesa, Siddi Ramulu; Rajesham, Bandari; Bhasker, Boyapally; Ashfaq, Mohd Ashraf; Khan, Aleem Ahmed; Rao, Sagurthi Someswar; Pal, Manojit
Abstract : Pyrano[3, 4- b ]indole fused quinoxalines were synthesized via an AlCl3 -mediated heteroarylation-cyclization method as potential anticancer agents. Abstract : An inexpensive, practical and one-pot method has been developed for the synthesis of quinoxalines fused with pyrano[3, 4- b ]indole, the central core of Lamellarin D. The methodology involved construction of the central pyranone ring via an AlCl3 -mediated heteroarylation-cyclization method. A number of compounds were prepared using this methodology, some of which were converted to the corresponding indol-3-ylquinoxaline derivatives. Several of the pyrano[3, 4- b ]indole fused quinoxalines showed promising growth inhibition of cervical and lung cancer cells and good interactions with topoisomerase I in silico .